طرق تعليم المحادثة في الهيئة اللغوية "الأزهار" بباري كديري جاوى الشرقية - Ritonga, Nur Ainun (Lisanul Arab: Journal of Arabic Learning and Teaching, 2021)
The researcher observed Al-Azhar Course, the one of Arabic Courses in Pare Kediri, East Java that . The reasons for establishing this language body are to assist students in practicing foreign languages, especially Arabic. Its purpose is for students to be able to speak Arabic. Its goal is to upgrade the competence of the Arabic language for Muslims so that they can speak this language and understand the Qur’an and Hadith and understand scientific literature and others. And her vision is a person with knowledge, good deeds, and decent morals. Its mission is to spread the Arabic language as a means of shaping the Islamic person with enthusiasm, intelligence and noble morals. The programs in the linguistic body “Al-Azhar” are from the dorm and the classroom, such as the “distinction” class, the class for the first stage, the class for the second stage, the class for the third stage, the curriculum class, and vacation programs. The methods used to teach conversation material in this linguistic form “Al-Azhar” in Bari Kediri East Java and in the classroom for the second stage, especially as follows: the audio-oral method, the direct method, the crazy method, the rhetorical method, and the problem-solving method.